Estimation of Shale Content Calculation using log data in Kutai Basin - Firmansyah, Yusi; Rafie, Muhammad; Ganjar Gaji, Reza Mohammad (Journal of Geological Sciences and Applied Geology, 2023)
Log data from the study area is located in the Kutai Basin, precisely in the Pulubalang Formation which is used to calculate the estimated shale content. Shale content estimation is one of the petrophysical parameters. In this study, the calculation of shale content estimation uses 3 methods, namely linear, Clavier and Stieber methods. The results of the calculation will provide the volume value of shale in the research area. In the process of calculating the shale content is calculated by separating the range of zones that will be calculated after determining the shale baseline by positioning the zone line on the highest gamma ray log and sand baseline on the lowest gamma ray which then shows the shale content contained in the zone to be analyzed. The results of the calculation of shale content in well A at a depth of 2750 - 3224 m ranged from 36.57% to 71.99%. The results of the analysis of clay content in the study area have an average clay content of 49.22%, meaning that the more clay content, the smaller the permeability and resistivity values will be and will increase the water saturation value.